Saving history : how white evangelicals tour the nation's capital and redeem a Christian America - Kerby, Lauren R. (Where religion lives., 2020)
"Millions of tourists visit Washington, D.C., every year, but for some the experience is about much more than sightseeing. Lauren R. Kerby's lively, engaging book takes readers onto tour buses and explores the world of Christian heritage tourism. These expeditions visit the same attractions as their secular counterparts-Capitol Hill, the Washington Monument, the war memorials, and much more-but the white evangelicals who flock to the tours are searching for evidence that America was founded as a Christian nation"--